Summary: Searching for a Democratic Equaliser: How Citizenship Education Moderates Inequalities in Internal Political Efficacy - Matthieu, Joke (Politics of the Low Countries, 2025)
Inclusiveness is a crucial pillar in democratic decision-making processes. This pillar rests on the equal political opportunities principle, which posits that every citizen should have an equal chance to influence political decisions. This democratic principle stands, however, in strong contrast to the inequalities among those politically active. One of political science research’s most stable and reliable findings is that privileged citizens participate more politically. Especially educational attainment is one of the best predictors of political participation (Willeck & Mendelberg, 2022). Scholars traditionally explain this by differential levels of resources (Verba et al., 1995). Due to disparities in resources such as time, money and cognitive sophistication, people have different barriers to taking up their civic rights. Education is traditionally believed to lower these barriers and increase the knowledge and skills necessary for political action.